The Relationship Between Sodium Consumption Patterns, Stress Levels, and Physical Activity with Hypertension of Elderly Participants at UPTD Puskesmas Rantau Tijang, Pugung District, Tanggamus Regency in 2022 - Ernawati, Dwi Testi (Sport and Nutrition Journal, 2023)
A person with hypertension has a rise in blood pressure above the healthy range of <120/<80. The amount of sodium that the body retains can impact blood prduction. Via the sympathetic nervous system's activation, which causes blood pressure to rise intermittently, stress causes hypertension. A sufficient amount of regular exercise significantly lowers blood pressure in hypertensive individuals. Elderly people frequently experience health issues. Many of these illnesses are non-communicable diseases like high blood pressure. The Province of Lampung has a 31,9% prevalence of hypertension. According to data on hypertension in the Tanggamus district, 120,276 persons have the condition. The research objective was to determine the correlation between sodium consumption patterns, stress levels, and physical activity with hypertension in prolanis participants at the Rantau Tijang Public Health Center, Tanggamus Regency in 2022. This study used quantitative research using a cross-sectional research design. The population in this study were 63 people using the total sampling technique. Bivariate analysis in this study uses the Gamma test. The results showed a significant correlation between the level of stress and physical activity and hypertension with a p-value of 0,001 and 0,003 and no significant correlation between sodium consumption and hypertension with a p-value of 0,746.